Exposure to styrene and mortality from nonmalignant respiratory diseases. Issue 7 (July 1996) - Welp, E; Partanen, T; Kogevinas, M; Andersen, A; Bellander, T; Biocca, M; Coggon, D; Gennaro, V; Kolstad, H; Lundberg, I; Lynge, E; Spence, A; et al.
Abstract : A cohort of 34, 560 men and 6128 women employed in 660 European factories manufacturing reinforced plastic products, followed up originally to assess the risk of cancer, was used to assess the risk of non-malignant respiratory diseases associated with exposure to styrene. Mortality from pneumonia was associated with intensity of exposure to styrene, but this may have been due to chance. Mortality from bronchitis, emphysema, and asthma was not associated with styrene exposure.